Vitamin D metabolites are lower with active Crohn's disease and spontaneously recover with development of remission. (July 2019) - Haifer, Craig; Lawrance, Ian C.; Center, Jacqueline R.; Clarke, Michael W.; Hart, Prue H.; Eisman, John A.; Lucas, Robyn; Ghaly, Simon
Background: Vitamin D deficiency is associated with active Crohn's disease (CD). However, it remains unclear if lower 25-hydroxyvitamin D [25(OH)D] concentration is the cause, or consequence, of intestinal inflammation. Existing literature has focused on circulating 25(OH)D rather than the active metabolite 1, 25(OH)2 D, or its breakdown product, 24, 25(OH)2 D. We aimed to characterise vitamin D metabolism in a cohort of patients with active and inactive CD. Methods: Fifty-four patients with CD and not on corticosteroids or vitamin D supplements, were enrolled in a 6-month prospective cohort study. Sera were collected on enrolment and at 6 months and tested for 25(OH)D, 1, 25(OH)2 D, 24, 25(OH)2 D using liquid chromatography tandem mass spectroscopy as well as vitamin-D-binding protein. Results: There were no differences in 25(OH)D or 1, 25(OH)2 D levels between participants with active versus inactive disease. Levels of 24, 25(OH)2 D were significantly lower in those with active compared with inactive disease (mean 3.9 versus 6.0 µmol/l; p = 0.007) and therefore the ratio of 25(OH)D:24, 25(OH)2 D was higher (mean 17.3 versus 11.1; p = 0.001). In those patients with active disease who achieved remission, there was a mean increase in 25(OH)D of 32.3 nmol/l (i.e. to a level in the sufficient range) and 24, 25(OH)2 D of 2.1 µmol/l. These increases were not seen in patients with persistently active or inactive disease. Conclusion: Levels of 24, 25(OH)2 D, but not 25(OH)D, were lower in patients with active CD, and spontaneously increased with resolution of underlying inflammation. The utility of 24, 25(OH)2 D as a biomarker of disease activity and vitamin D status in CD warrants further exploration.